BACILLUS STRATOSPHEARICUS SP. ISOLATED FROM AIR SAMPLES OF HIGH ALTITUDE - ANANIA ARJUNA (International Journal of Pharma and Bio Sciences, 2014)
A novel bacterial strains were isolated from air samples at altitudes of 30 km. The strain was identified as members of the genus Bacillus. Phylogenetic analysis based on 16S rRNA gene sequences indicated that the strain indicated a similarity of 98–99% with Bacillus licheniformis and 98% with Bacillus sonorensis. Strain showed 100% 16S rRNA gene sequence similarity to Bacillus pumilus, but differed from its nearest phylogenetic neighbour in a number of phenotypic and chemotaxonomic characteristics and showed only 55% DNA–DNA relatedness. Therefore, the isolate represented novel species of Bacillus stratosphericus sp. nov.